Accuracy Of Open-Wedge High Tibial Osteotomies: Comparison Of Radiologic Outcomes Between 2 Techniques Using Hernigou's Table Vs Conventional Method. Issue 5 (31st May 2019) - Nicolau, Xavier; Bonnomet, François; Favreau, Henri; Adam, Philippe; Ehlinger, Matthieu
Objectives: Long-term outcomes of patients who suffer from medial osteoarthritis, who were treated with a medial open-wedge high tibial osteotomies (HTO) depend on the final hip-knee-ankle angle (HKA) obtained after surgery. A 2 to 4° postoperative valgus objective is usually admitted. Many surgical techniques are described to reach this target range. The purpose of this study was to compare the accuracy of the post-surgical correction achieved compared to the predetermined correction goal of two different surgery technique: Hernigou's table (HT) vs conventional method (CM). Methods: In this retrospective monocentric study, 38 patients who were managed with an open-wedge HTO for medial osteoarthritis were included, from 01/2009 to 01/2014: 21 were treated using the « HT » and 17 using a « CM ». There were 24 men and 14 women, with a median age of 48 [31; 61] years old, and a median BMI of 30 [25; 40] kg/m2. There was one single operator for each group, expert in the surgical technique used. The intended correction was individually defined for each patient. The surgical accuracy, where small values represent greater accuracy, was defined as the absolute deviation of the intended correction from the achieved correction, measured on the average HKA angle on postoperative long-leg alignment films with bipodal weight bearing. Results: The median intended correction was 13° [10; 18] and 10° [5; 17] in the « CM » and « HT » respectively. The median surgical accuracy was 2, 63° [0, 2; 6, 4] for « CM » compared to 0, 9° [0, 1; 3, 7] for « HT » with statistical significance (p=0, 02). In the conventional group, there were 65% (11/17) of outliers (>2° from the intended correction) compared to 29% (6/21) in the « HT » group, with statistical significance (p=0, 048). One revision in « HT » groups was needed for nonunion, with consolidation achieved, Conclusion: For coronal plane corrections, Hernigou's table method was shown to have a greater accuracy to reach the intended correction. Unidimensional radiological analysis, however, becomes disgraced by the advent of three-dimensional planning or navigation, but remains an accessible and simple means of planning.